2014
DOI: 10.1111/jcmm.12325
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of DACH1 induces the invasion and metastasis of gastric cancer by activating TGF‐β signalling

Abstract: Gastric cancer (GC) is the fourth most common malignancy in males and the fifth most common malignancy in females worldwide. DACH1 is frequently methylated in hepatic and colorectal cancer. To further understand the regulation and mechanism of DACH1 in GC, eight GC cell lines, eight cases of normal gastric mucosa, 98 cases of primary GC and 50 cases of adjacent non-tumour tissues were examined. Methylation-specific PCR, western blot, transwell assay and xenograft mice were used in this study. Loss of DACH1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…As to the clinical-pathological relevance of DACH1 in NSCLC, we observed that DACH1 abundance was inversely corelated with tumor stage, grade and metastasis, which is consistent with previous reports [10,12-14,23]. Thus far, only a handful of reports have explored the value of DACH1 as a molecular marker for cancer prognosis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As to the clinical-pathological relevance of DACH1 in NSCLC, we observed that DACH1 abundance was inversely corelated with tumor stage, grade and metastasis, which is consistent with previous reports [10,12-14,23]. Thus far, only a handful of reports have explored the value of DACH1 as a molecular marker for cancer prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…Recent findings supported the role of DACH1 as a novel tumor suppresor in several kinds of human cancers [5,12-25]. The link of DACH1 to lung cancer was initially uncovered by whole-genome and transcriptome sequencing of NSCLC samples.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Subsequently, DACH1 was found to restrain TGF-β/SMAD-induced EMT [50]. DACH1 may also antagonize EMT in part by inactivating Wnt/β-catenin signaling; indeed, DACH1 was recently found to downregulate β-catenin in hepatocellular and gastric cancer [35, 51].…”
Section: The Rdgn In Tumor Initiation and Progressionmentioning
confidence: 99%
“…For example, expression of DACH1 inhibited epithelial-mesenchymal transition and metastasis by inhibiting TGF-β-induced signaling. 65 Tumor size was reduced in xenografted mice with DACH1-expressing BGC823 cells. TGF-β-induced epithelial-mesenchymal transition was also noted in ovarian cancer HEYC2 cells, by increasing both expression and activity of DNMT1, DNMT3A, and DNMT3B.…”
Section: Transforming Growth Factor Signalingmentioning
confidence: 99%